2007
DOI: 10.1194/jlr.m600457-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of high density lipoprotein particles with membranes containing cholesterol

Abstract: In this study, free cholesterol (FC) efflux mediated by human HDL was investigated using fluorescence methodologies. The accessibility of FC to HDL may depend on whether it is located in regions rich in unsaturated phospholipids or in domains containing high levels of FC and sphingomyelin, known as "lipid rafts." Laurdan generalized polarization and two-photon microscopy were used to quantify FC removal from different pools in the bilayer of giant unilamellar vesicles (GUVs). GUVs made of POPC and FC were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 64 publications
8
62
0
1
Order By: Relevance
“…In lipid membranes the Laurdan probe is sensitive to the amount of water molecules present within the bilayer. If the lipids are ordered, water molecules will have less access to the probes embedded in the membrane, thus resulting in a high value of GP [29]. The results we obtained indicate that Q extract causes increased packing order of the lipid heads at the membrane interphases.…”
Section: Packing Order and Fluidity Of Membranesupporting
confidence: 62%
“…In lipid membranes the Laurdan probe is sensitive to the amount of water molecules present within the bilayer. If the lipids are ordered, water molecules will have less access to the probes embedded in the membrane, thus resulting in a high value of GP [29]. The results we obtained indicate that Q extract causes increased packing order of the lipid heads at the membrane interphases.…”
Section: Packing Order and Fluidity Of Membranesupporting
confidence: 62%
“…This shift can be quantified as values ranging between -1 and 1 using the GP function 134 . All bilayers of the polymerosomes appeared bluish indicating that they are significantly more hydrophobic than DOPC liposomes which appeared green 95 , see Figure 11.…”
Section: Polaritymentioning
confidence: 99%
“…42 ), and their effects on membrane properties have been explored using laurdan GP analysis. It has been shown that MbCD increases the fl uidity of biological membranes as assessed by a signifi cant reduction of laurdan GP ( 43 ).…”
Section: C-laurdan Gp Measurements In Guvsmentioning
confidence: 99%